2018
DOI: 10.1007/978-3-030-00151-3_3
|View full text |Cite
|
Sign up to set email alerts
|

TCTL Model Checking Lower/Upper-Bound Parametric Timed Automata Without Invariants

Abstract: We study timed systems in which some timing features are unknown parameters. First we consider Upper-bound Parametric Timed Automata (U-PTAs), one of the simplest extensions of timed automata with parameters, in which parameters are only used as clock upper bounds in the constraints. Up to now, there have been several decidability results for the existence of parameter values in U-PTAs such that flat TCTL formulas are satisfied. We prove here that this does not extend to the full logic and that only one level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…With the notable exception of [JLR15,ALR18], and to some extent of [BLT09] which addresses the existence of cycles, all the works cited above focus on safety properties, through the basic problem of reachability. This is maybe not so surprising given that most results related to this simpler problem are already negative.…”
Section: Decidability Of Ptasmentioning
confidence: 99%
See 1 more Smart Citation
“…With the notable exception of [JLR15,ALR18], and to some extent of [BLT09] which addresses the existence of cycles, all the works cited above focus on safety properties, through the basic problem of reachability. This is maybe not so surprising given that most results related to this simpler problem are already negative.…”
Section: Decidability Of Ptasmentioning
confidence: 99%
“…On the positive side, exact synthesis algorithms are proposed for reachability properties in L-PTAs and U-PTAs over integer-valued parameters in [BLT09]. On the negative side, it is shown in [ALR18] that the full TCTL-emptiness problem (i. e., the emptiness of the valuation set for which a particular TCTL formula is satisfied on the model) is undecidable even for U-PTAs. IMITATOR [And21] for PTAs, and Roméo [LRST09] for PTPNs.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we showed that the emptiness-problem using nested quantifiers (i.e. beyond EF, EG, AF, AG) automatically leads to the undecidability, even for the very restricted class of U-PTAs with a single parameter (that can even be integer-valued) [ALR18]. In other words, the nested TCTL emptiness problem is undecidable for U-PTAs.…”
Section: The Class Of L/u-ptasmentioning
confidence: 96%
“…We exhibit in this section a nested TCTL formula (by opposition to flat TCTL formula, e. g., EF or AF), namely EGAF =0 ap for some atomic property ap and prove that EGAF =0 -emptiness is undecidable for (possibly bounded) PTA U I . The formula EGAF =0 was already used to prove the TCTL-emptiness of U-PTAs in [ALR18]. This implies the undecidability of the whole TCTL-emptiness problem for (possibly bounded) PTA U I .…”
Section: B Undecidability Of Tctl-emptinessmentioning
confidence: 99%